STUDI PERBANDINGAN PEMBELAJARAN MEMBACA PERMULAAN BAGI SISWA BERKEBUTUHANÂ Â KHUSUS DI SDNÂ INKLUSIF - NIRWANA, (Jurnal Pendidikan Khusus, 2016)
Abstract Special need children had different reading ability in SDN inclusion 1 Selong and SDN inclusion 2Suangi East Lombok i.e. the reading ability of special need students in SDN inclusion 1 Selong was better than the special need students in SDN inclusion 2 Suangi. Based on the fact, the research was done to know the difference of learning beginning reading of special need students in SDN inclusion 1 Selong and SDN inclusion 2 Suangi East Lombok involving: (1) learning plan (RPP and PPI), (2) learning implementation including material, method, media, and evaluation, (3) reading skill of special need students. The purpose of this research was directed to describe the difference and the similar of learning beginning reading of special need students in SDN inclusion 1 Selong and SDN inclusion 2 Suangi scoping 1) learning plan (RPP and PPI), 2) learning implementation including material, method, media, and evaluation, 3) reading skill of special need students. This research was descriptive qualitative. The data collection was done by Triangulation Validation method. The data analysis was done by flow technique those were data reduction, display data (presenting data), and conclusion / verification. Based on the research result it could be concluded that there were difference and similar of learning beginning reading between SDN inclusion 1 Selong and SDN inclusion 2 Suangi. The difference existed related with learning media and the ability of reading skill of special need students and the similar existed related with learning plan, material, method, and learning evaluation.   Keywords: studi comparison, beginning reading